2019
DOI: 10.1002/slct.201902908
|View full text |Cite
|
Sign up to set email alerts
|

Role of X‐ray Scattering Techniques in Understanding the Collagen Structure of Leather

Abstract: This review focuses on the SAXS and WAXS analysis of the collagen structure of leather, from pioneering works through to recent developments. X-ray scattering can be used to investigate the structural features of fibrillar collagen in the leather matrix, including axial periodicity, fibril diameter, chemical fixation, hydration and fibrillar orientation. Key properties of leather, such as appearance, handle, strength, hydrothermal stability and resistance to putrefaction, are closely linked to these parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 73 publications
3
12
0
Order By: Relevance
“…2(b)]. The increase in overall peak intensity confirmed the synthetic crosslinking effect by chromium sulfate, in agreement with previous reports (Buchanan et al, 2019). The intermolecular packing of collagen follows a quarter-staggered arrangement, resulting in a gap and overlap banding structure with a characteristic periodicity in the axial direction (D-period) (Petruska & Hodge, 1964).…”
Section: Effect Of Natural and Synthetic Crosslinks On Collagen Strucsupporting
confidence: 89%
See 1 more Smart Citation
“…2(b)]. The increase in overall peak intensity confirmed the synthetic crosslinking effect by chromium sulfate, in agreement with previous reports (Buchanan et al, 2019). The intermolecular packing of collagen follows a quarter-staggered arrangement, resulting in a gap and overlap banding structure with a characteristic periodicity in the axial direction (D-period) (Petruska & Hodge, 1964).…”
Section: Effect Of Natural and Synthetic Crosslinks On Collagen Strucsupporting
confidence: 89%
“…However, it is essential to understand the interplay between natural and synthetic crosslinks and their contribution to the heat stability of collagen structure, which still remains unclear. Using synchrotron-based small-angle X-ray scattering (SAXS), changes in the collagen structure during crosslinking and denaturation can be monitored in situ (Buchanan et al, 2019). Also, liquid chromatography-mass spectrometry (LC-MS) can be used to quantify the natural crosslinks present in skin collagen (Naffa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We found that a decrease in D -periodicity from 65.44 nm to around 65.2 nm occurred after cross-linking, indicating that the collagen molecules are drawn closer together by the inter-molecular and intra-fibril cross-linking of DCMC with its small size (Table ), allowing its penetration through the lateral and axial gaps of the collagen molecules in the fibrils . The peak positions and intensities obtained from the SAXS spectrum are known to be associated with the cross-linking and dehydration of collagen fibers . The relative intensity of the fifth to third order peak ( R 5/3 ) was related to the covalent cross-linking between the cross-linking agent and collagen .…”
Section: Resultsmentioning
confidence: 92%
“…39 The peak positions and intensities obtained from the SAXS spectrum are known to be associated with the cross-linking and dehydration of collagen fibers. 40 The relative intensity of the fifth to third order peak (R 5/3 ) was related to the covalent cross-linking between the cross-linking agent and collagen. 38 The relative intensity of the sixth to fifth order peak (R 6/5 ) represented the dehydration of collagen due to the displacement of water by the cross-linking agent through non-covalent interactions.…”
Section: Resultsmentioning
confidence: 99%
“…44 Even though the general chemistry used in hide and skin processing is well-known, the structural changes at the level of the collagen fibrils is just starting to be revealed utilizing x-ray scattering techniques. [45][46][47] Herein we focused on the macroscopic effect of the composition of the soaking solutions on water sorption by horsehide and the correlations with the properties of corresponding final leather material.…”
Section: Water Absorption By Horsehidementioning
confidence: 99%